Gains derived from illegal activities :an analysis of the taxation consequences - Mtshawulana, Lungiswa Bukeka (Rhodes University, Faculty of Commerce, Department of Accounting, 2009)
Income Tax in South Africa is levied in terms of the Income Tax Act 58 of 1962 on taxable income, which, by definition, is arrived at by deducting from "gross income" receipts and accruals that are exempt from tax as well as deductions and allowances provided for in the Act. The Income Tax Act provides no guidance with regard to the taxation of illegal activities, except to prohibit the deduction of expenditure incurred in paying fines or in relation to corrupt activities, as defined. An analysis of the taxation of income derived from theft, fraud and prostitution and the deductibility of expenses relating to that income, is the question addressed in this thesis. In this thesis, an analysis was made of relevant case law in relation to the provisions of the Income Tax Act in an attempt to provide clarity. A brief comparison was also macie of American, United Kingdom and South African tax law. Similarities were found between the American, United Kingdom and South African tax regimes in relation to the taxation of income, but there appeared to be more certainty in America and the United Kingdom in relation to the deduction of expenses. The thesis concludes that recent case decisions have provided certainty in relation to income from illegal activities, but the tax status of the deduction of expenses remains uncertain.
Keywords: Uncatalogued